2021
DOI: 10.1002/onco.13914
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Adjuvant Therapy Versus Surgery Alone for Stage IIB–III Esophageal Squamous Cell Carcinoma: A Phase III Randomized Controlled Trial

Abstract: Background. Retrospective studies have shown that adjuvant treatment improves survival of patients with stage IIB-III esophageal squamous cell carcinoma, but there is no evidence from prospective trials so far. Methods. Patients with pathological stage IIB-III esophageal squamous cell carcinoma were randomly assigned to receive surgery alone (SA), postoperative radiotherapy (PORT), or postoperative concurrent chemoradiotherapy (POCRT). PORT patients received 54 Gy in 27 fractions; POCRT group received 50.4 Gy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 32 publications
(62 reference statements)
1
23
0
1
Order By: Relevance
“…According to the prospective randomized controlled trial by Ni et al. ( 43 ), for patients with pathological stage IIB–III esophageal squamous cell carcinoma after radical surgery, POCRT, which reduced the radiation field to 3 cm below the carina and reduced the radiation dose to 50.4 Gy, did not increase the in- or out-of-field recurrence. Additionally, the survival rate was more comparable than with the PORT.…”
Section: Discussionmentioning
confidence: 99%
“…According to the prospective randomized controlled trial by Ni et al. ( 43 ), for patients with pathological stage IIB–III esophageal squamous cell carcinoma after radical surgery, POCRT, which reduced the radiation field to 3 cm below the carina and reduced the radiation dose to 50.4 Gy, did not increase the in- or out-of-field recurrence. Additionally, the survival rate was more comparable than with the PORT.…”
Section: Discussionmentioning
confidence: 99%
“…Lv et al 6 reported 3‐year OS of 63% for ACCRT versus 51% for observation, whereas 65% versus 47% was observed in our study after PSW adjustment. In another recently published RCT (also limited by lack of mandatory PET), Ni et al 25 reported 3‐year OS of 66.5% for ACCRT versus 48% for observation ( p = 0.016). Hsu et al 26 reported the HR of death to be 0.63 when ACCRT was compared to observation, whereas we found the HR of death to be 0.58 in our study.…”
Section: Discussionmentioning
confidence: 99%
“…A phase III randomized controlled trial in China has demonstrated that postoperative treatment (PORT/POCRT) may significantly prolong the survival in these patients. The pathological TNM stage and treatment regimen can significantly affect the DFS and OS ( Ni et al, 2021 ). In our study, the TNM stage was also found as an independent prognostic factor for OS and DFS, but the predictive capability for survival was poor.…”
Section: Discussionmentioning
confidence: 99%
“…According to Xiao’s research conclusion, postoperative radiotherapy can effectively reduce the probability of locoregional recurrence for all patients and can improve the survival of stage III or positive lymph node metastatic esophageal carcinoma ( Xiao et al, 2003 ; Xiao et al, 2005 ). A randomized controlled trial of phase III suggested that postoperative radiotherapy, especially postoperative chemoradiotherapy, significantly improved DFS and OS in stage IIB–III esophageal squamous cell carcinoma ( Ni et al, 2021 ). Even for patients with relatively early-stage T2–3N0M0, it was also well documented that postoperative radiotherapy significantly increased the patients’ DFS and reduced the likelihood of the local regional recurrence rate ( Deng et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%